Trace Determination of Tetrabromobisphenol A in Water Samples with Temperature Controlled Ionic Liquid Dispersive Microextraction - Yuan, J.P.; Liu, J.H.; Wang, S.S.; Cui, Z.J. (Asian Journal of Chemistry, 2012)
A sensitive method based on temperature controlled ionic liquid dispersive microextraction combined with high performance liquid chromatography-electrospray tandem mass spectrometry (HPLC-ESI-MS-/MS) has been developed for the determination of trace tetrabromobisphenol A in water samples. In temperature controlled ionic liquid dispersive microextraction, toxic organic solvents for extraction and dispersion were free. Some important factors that may be influence the extraction recovery were investigated and optimized. Under the optimum conditions, excellent linearity was obtained in the range of 0.5-50 μg L-1 with correlative coefficient (R) 0.9987. The limit of detection was 0.05 μg L-1 and the relative standard deviation (RSD) was 7.70 % (n = 6). The proposed method was successfully applied to analyze real environmental water samples. The satisfactory spiked recoveries were in the range of 92.4-103.9 % and relative standard deviations were in the range of 3.31-8.68 %.